PENGARUH FREKUENSI SENAM DIABETES MELITUS TERHADAP KADAR GULA DARAH (Studi pada Kelompok Umur ≥ 45 Tahun di Kota Semarang) - Adriana Rizki Novita; Apoina Kartini; Siti Fatimah Pradigdo (Jurnal Kesehatan Masyarakat (Undip), 2018)
Changes in blood sugar levels is caused by physical activity. Muscles that are active due to physical activity can increase the number of insulin receptors and the sensitivity of receptors to insulin. The purpose of this study is to analyze the effect of Diabetes Mellitus exercises on blood sugar level in age group ≥ 45 years in Semarang City. This research is Quasi Experimental research with Non Equivalent Control Group Design consists of a control group (exercises 1 time a week in KJS Gempita) and intervention group (exercises 3 times a week in KJS Sampangan Indah). The sampling technique used purposive sampling, the sample size of each group is 25 respondents with the criteria of the age group ≥ 45 years and not smoking. Blood sugar level respondent checked by Humalyzer conducted in one of the private laboratory in Semarang. Different test using Wilcoxon Signed Rank Test, Mann Whitney, Independent T-test and Chi Square. There was a difference blood glucose levels pre-post mean of intervention group (p=0,014) and difference changes in blood sugar levels mean of both group (p=0,016). Changes in blood sugar levels are not only influenced by the frequency of exercises, but also age, nutritional status, and diet. The results of this study that for the age group ≥ 45 years of exercises 1 times a week is more effective to control or lower blood sugar levels. Recommendations for respondents is to reduce consumption of high fat foods and exercise recommended should be 1 times a week.